Congenital hypothyroidism, spiky hair, and cleft palate. Issue 1 (January 1989) - Bamforth, J S; Hughes, I A; Lazarus, J H; Weaver, C M; Harper, P S
Abstract : Two brothers are described with athyroidal hypothyroidism, spiky hair, choanal atresia, cleft palate, and bifid epiglottis. Polyhydramnios was present in the third trimester of each pregnancy. These abnormalities appear to represent a new syndrome.